Stem cell MicroRNAs in senescence and immortalization: novel players in cancer therapy. Issue 1 (26th July 2011) - Leal, Jose A.; Feliciano, Andrea; LLeonart, Matilde E.
<x xml:space="preserve">Abstract</x> The molecular etiology of malignancy remains one of the most challenging disease processes under scientific investigation; therefore, improved approaches for their treatment are urgently needed. MicroRNAs are highly conserved nonprotein‐coding RNAs that regulate gene expression. They are involved in important homeostatic processes, such as cellular proliferation, cell death and development, and affect many diseases, including cancer. High‐throughput screenings based on microRNAs related to senescence/immortalization are potential tools for identifying novel proliferative microRNAs that might be involved in carcinogenesis. Recently, a subgroup of highly proliferative microRNAs, which belong to a cluster expressed exclusively in embryonic stem cells and their malignant derivatives (embryonic carcinoma cells), was revealed to play a role in senescence bypass, thereby providing immortalization to human cells. This finding supports the cancer stem cell theory and the relevance of microRNAs in human tumors. This article recapitulates the role of microRNAs that are associated with stem cell properties and their possible link in common pathways related to immortalization and cancer. Ultimately, cancer therapy that is based on the induction of a senescence response is proposed to be highly associated with the loss of stemness properties. Thus, it would be possible to "kill two birds with one stone": along with the inhibition of stemness properties in cancer stem cells, the senescence response could be induced to destroy the cancer stem cell population within a tumor. © 2011 Wiley Periodicals, Inc. Med Res Rev